P292 Monitoring adults with chronic pancreatitis – are we doing it right?. (19th June 2022) - Poon, Dennis; Baxter, Andrew; Alabraba, Edward
Abstract : Introduction: Chronic pancreatitis (CP) is a progressive, life-limiting disease with a median survival of 20 years. The estimated population prevalence is 163 per 100, 000 based on UK Biobank data. Most patients will have developed pancreatic exocrine and endocrine insufficiency with the development of diabetes within 10 and 20 years after diagnosis, respectively. Patients with CP are often malnourished with a low body mass and deficient in fat-soluble vitamins and minerals. Osteopenia and osteoporosis is common and can be detected by bone density testing. The National Institute for Health and Care Excellence (NICE) recommend that patients with CP should be screened for diabetes every six months, pancreatic exocrine insufficiency (PEI) and a malnutrition assessment at least every 12 months, and osteopenia/osteoporosis every two years. Methods: We retrospectively reviewed the medical records of 50 adult patients, in sequential order of their hospital numbers, from our existing database of patients with CP in the Nottinghamshire region. All patients had been reviewed by a gastroenterologist, hepatobiliary surgeon or endocrinologist at some point within the last 5 years but not all were under active follow up in secondary care. Tests performed in the most recent two years to screen for PEI, diabetes, malnutrition and reduced bone density were recorded and frequencies of these tests conducted were assessed against the NICE recommendations. Results: Haemoglobin A1c (HBA1c) was monitored every six months in 36 patients (72%). 38 patients were on pancreatic enzyme replacement (76%) and of the remainder only one out of 12 (8%) had faecal elastase-1 as a screening test for PEI within the last year. 31 patients (62%) had some form of biochemical malnutrition screen but only one patient (0.5%) had a full assessment with all fat-soluble vitamins and minerals checked within the last year. Two patients (1%) underwent a dual-energy X-ray absorptiometry (DEXA) scan to assess their bone densities within the last two years. Conclusions: Regional monitoring of patients with CP is suboptimal. Published national audit data are lacking but it is probable that the overall care of these patients across the country proves to be similar. Our study highlights that improvement to the long-term care of this patient group is urgently needed and a multidisciplinary approach involving at least a clinician, a dietitian and a nurse specialist with an interest in CP may be required in managing these complex patients which is probably best situated in secondary care.